New Insights into the Biology, Ecology, and Management of Mosquitoes - Athanasios Giatropoulos (Insects)
Mosquitoes pose a great threat to human and animal health as vectors of many important diseases such as malaria, dengue, West Nile virus, yellow fever, filariasis, and encephalitis [...]